Quality of life for social care centre clients - Alondere, Linda; Kaulina, Anda; Juhnevica, Renate (Magyar Gerontológia, 2021)
Introduction:There are approximately 60 million people over 60 years of age in the world. The United Nations predicts that by 2050 the number of people aged 60 years and older could be around 2 billion (Zaļkalns, 2015). In Latvia, every fourth inhabitant is a pensioner. Given Latvia's socio-economic situation, social and health care options for older, lonely people are becoming increasingly less accessible. A large part of the population of Latvia cannot provide themselves with quality of life in old age. If there is no family or, due to various circumstances, relatives cannot take care of the elderly, the only option is social care institutions (Slokenbeka, Zepa, 2013). The quality of life of an elderly person remains an issue when he or she is in a social care centre. Quality of life is a complex, interacting set of objective and subjective indicators in different areas of life. The World Health Organisation defines quality of life as “the perception of an individual's personal life position in the context of the cultural and value system in which the individual lives in relation to the individual's goals, expectations, standards and concerns. It is a broad concept that is influenced in complex ways by a person's physical health, psychological state, personal beliefs, social relationships and key environmental factors” (Scester, 2012).The Aim of the study:To analyse the quality of life for social care centre clients.Materials and methods:Quantitative research method was chosen to obtain the results. A questionnaire with 25 questions was developed. The participants of the research were clients of two social care centres (hereafter SAC) (SAC “X”, n = 50; SAC “Y”, n = 50).Results:The majority of SAC respondents have lived in the institution for more than four years (SAC “X” = 54%; SAC “Y” = 70%). In both groups, the predominant reason for being in SAC is “I am lonely, I cannot take care of myself” (SAC "X" = 62%; SAC "Y" = 58%). On the questions about the frequency of meals and the quality of food in the SAC, the data show that 78% of clients in SAC “X” and 94% in SAC “Y” are satisfied with the frequency of meals, while on the quality of food the dominant answer is “the food is satisfactory” (SAC “X” = 54%; SAC “Y” = 32%). The questions on living conditions show that SAC clients live both alone and in pairs (mainly spouses). The relationship with the roommate is described by 52% in SAC “X” and 38% in SAC “Y” with the phrase “we get along peacefully, without quarrels”. 26% of respondents in both groups describe their relationship as “very good and friendly”. SAC clients describe their financial situation as “modest”. Emotional support is received from other residents, staff and family members/relatives. Emotional uplift is also provided by various activities in the SAC and by doing things that they enjoy and find interesting, e.g., handicrafts, crossword puzzles. SAC clients note that they try to attend all events organised by the SAC, especially concerts by amateur groups and famous artists. The “feeling of security” in the SAC is prevalent in both groups of respondents (SAC “X” = 56%; SAC “Y” = 70%). Although there is a feeling of security, both groups of respondents report that they “miss the feeling of home” when living in SAC (SAC “X” = 24%; SAC “Y” = 34%).Conclusions:Clients in the social care centre are satisfied with the quality of life in the physical and social spheres, but are partially satisfied or dissatisfied with the quality of life in the emotional and area of independence. The participants often feel lonely and sad and experience longing and anticipation. Respondents in both social care centres never or rarely experience feelings such as love, joy and happiness. Respondents indicate a lack of independence, acknowledging that they have limited autonomy and that they cannot be who they are because they have to adapt to the existing regime.Bibliography:1. Zaļkalns J. (2015). Novecošana – aktualitātes un problemātika. Retrieved 25 January 2017 from http://www.afonds.lv/editor/uploads/files/prezentacijas/1_Zalkalns_Novecosana_aktualitates_ problematika.ppt2. Slokenbeka A., Zepa D. (2013). Vecums – liktenis, izaicinājums, dāvana. Rīga: RAKUS Atbalsta fonds. 96 lpp3. Šķestere, I. (2012). Pētījums par dzīves kvalitātes izvērtējuma metodēm un instrumentiem. Rīga: ES Eiropas Sociālais fonds. 43 lpp.